E-MUL: Model Edukasi Digital untuk Meningkatkan Literasi Keuangan dan Pendapatan UMKM Berbasis Mobile Learning di Kabupaten Sedang Bedagai - Yenni Arfah; Suwadi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the Indonesian economy, including in Serdang Bedagai Regency, making this sector a key driver of local economic growth. However, most female MSMEs still face challenges in financial literacy, particularly in cash flow recording, capital management, and financing decision-making. This study aims to develop a Green Economy-based Digital Microfinance conceptual model designed to improve financial literacy and strengthen access to capital for female MSMEs in rural areas. The method used is Research and Development (R&D), which includes problem identification, literature review, model design, and limited trials. The results show that the developed model combines three main components: (i) microfinance literacy, which improves transaction recording skills by up to 30% with an average increase in literacy scores of 22%; (ii) integration of green economy principles, which encourages 65% of business actors to consider resource efficiency and environmental sustainability practices; and (iii) a mobile learning approach, which was positively appreciated by 88% of respondents because it provides flexible access and accelerates material understanding. Overall, this model has proven relevant in addressing the financial literacy needs of women-led MSMEs in rural areas, while also offering a new direction in empowering micro-enterprises oriented toward sustainability.